Exploiting Joint-Resident Stem Cells by Exogenous SOX9 for Cartilage Regeneration for Therapy of Osteoarthritis - Zhang, Xiaowei; Wu, Shili; Zhu, Yong; Chu, Cong-Qiu (Frontiers in Medicine, 2021)
The lack of effective treatment options for osteoarthritis (OA) is mostly due to the very limited regenerative capacity of articular cartilage. Mesenchymal stem cells (MSCs) have been most extensively explored for cell-based therapy to induce cartilage regeneration for OA. However, current in vitro expanded MSC-based approaches have significant drawbacks. On the other hand, osteoarthritic joints contain chondrocyte progenitors and MSCs in several niches which have the potential yet fail to differentiate into chondrocytes for cartilage regeneration. One of the underlying mechanisms of the failure is that these chondrocyte progenitors and MSCs in OA joints are deficient in the activity of chondrogenic transcription factor SOX9 (SRY-type high-mobility group box-9). Thereby, replenishing with exogenous SOX9 would reactivate the potential of these stem cells to differentiate into chondrocytes. Cell-permeable, super-positively charged SOX9 (scSOX9) protein is able to promote hyaline-like cartilage regeneration by inducing chondrogenic differentiation of bone marrow derived MSCs in vivo. This scSOX9 protein can be administered into osteoarthritic joints by intra-articular injection. This one-step, cell-free supplement of exogenous SOX9 may harness the regenerative potential of the intrinsic MSCs within the joint cavity to stimulate cartilage regeneration in OA.